Democratic Leadership and Decisions Making on Education in Islamic Perspective - Aldo Redho Syam; Achmad Supriyanto; Mustiningsih Mustiningsih (Cendekia: Kependidikan dan Kemasyarakatan, 2020)
Abstract: This research aimed to determine democratic leadership and decisions making on education in Islamic perspective at Madrasah Ibtidaiyah Pesantren Anak Sholeh Baitul Qur’an Gontor Ponorogo. This research used descriptive qualitative research with data collection methods through interviews, observations, and documentation, as well as Miles and Hubberman data analysis, including data analysis, data presentation, and drawing conclusions. The results of this research indicate that democratic leadership principal of school and making decisions on education in Islamic perspective at Madrasah Ibtidaiyah Pesantren Anak Sholeh Baitul Qur’an Gontor Ponorogo has been carried out properly in accordance with Quran, in Ash-Shura: verse: 38, which is reflected in every decision. The school principal always decides through a deliberative forum together with the teachers openly, responsively, responsibly, and trustfully, by promoting the principle of togetherness and kindship.  ملخص: الهدف من هذا البحث هو معرفة قيادة الديمقراطية ووضع السياسات والقرارات التعليمية علي نظرية الإسلام في المدرسة الابتدائية معهد ولد الصالح بيت القرآن فونوروكو. يستخدم هذا البحث البحث النوعي الوصفي مع أسلوب جمع البيانات من خلال المقابلات والملاحظات والتوثيق، وكذلك استخدام تحليل بيانات على نموذج ميليس وهوبيرمين، الذي يشمل على تحليل البيانات، وعرض البيانات، وأخذ الاستنباط. تشير نتائج هذا البحث إلى أن: قيادة الديمقراطية مدير المدرسة ووضع السياسات والقرارات التعليمية في المدرسة الابتدائية معهد ولد الصالح بيت القرآن فونوروكو، تم تنفيذها بشكل جيد ومناسب بالقرآن في سورة الشورى: الآية ٤٣، ويظهر ذلك عند ما توجد مشكلات التعليم والتربية، فالمدير يحلها دائما من خلال التشاور مع المعلمين منفتحا، ومستجيبا، ومسؤولا،  بتقديم مراعاة مبدأ العمل الجماعي والأسري.